Avaliação de áreas queimadas no Parque Nacional das Sempre-Vivas MG: contribuições para a implantação do manejo integrado do fogo - Tereza Beatriz Oliveira Soares (2016)
The fire presence in protected areas, especially those inserted in the Cerrado, is constituted as a great challenge for managers. Since the creation of the Brazilian Protected Areas (PA), the zero fire policy has been practiced, which made this dynamic of combustible material accumulation be repeated numerous times, spreading catastrophic fires over the years. Facing this scenario, a new concept of fire has been discussed by environmental agencies. The Integrated Fire Management (IFM) gains ground as it is understood that the fire combat and the policy adopted are not generating satisfactory results. Considering this, the purpose of this research is to generate information by using remote sensing and data collected in the field that can contribute to the IFM implementation in the Sempre-Vivas National Park. Therefore, the mapping of burned areas was done during the period 2000-2015 to understand the fire dynamics in this protected area. Data from sensors of series Landsat were used for burn scars delimitation. From this survey a fire frequency map was generated for the period analyzed. Furthermore, hotspots products from Moderate Resolution Imaging Spectroradiometer (MODIS), products MOD14A1 and MYD14A1, as well as Tropical Rainfall Measuring Mission (TRMM) precipitation data, product 3B43V6, were used to verify the influence of rain in the incidence of fires. Moreover, Enhanced Vegetation Index (EVI) was used to understand the dynamics of vegetation. Two field surveys were conducted with the aim of following the first prescribed burnings that happened in the IFM and participating in the evaluation phase of the project implementation, as well as the application of semi-structured interviews with public servants from the Sempre-Vivas National Park and surrounding community. Results show that during the past 16 years approximately 22,000 hectares were burned inside the park and that there was an incidence of almost 1,000 fire spots in that period. The extreme events occurred in the years 2003, 2007 and 2011. From the frequency map it was observed that some areas burned up to 10 times out of 16 years. With Vegetation Index we analyzed the vegetations dynamics and where it is concentrated on the territory of Sempre-Vivas National Park. The data demonstrated that precipitation can influence the occurrence of fires. However, it does not determine the years with greater or lesser occurrence of fire. During the first field, biomass and fire temperature data from the first prescribed burn was produced, while in the second field elements on the perception of management, employees and community among other issues were collected from the meeting with managers and the interviews. The IFM inaugurates a new concept of fire in Brazilian protected areas and, thus, deserves attention of researchers in order to advance the knowledge on the subject.